APPLICATION OF STUDENT FACILITATOR AND EXPLAINING MODEL IN LEARNING - Afandi Afandi; Mudmainnah Mudmainnah (Molang: Journal Of Islamic Education, 2024)
This study examines the application of the Student Facilitator and Explaining (SFE) Model in learning fiqh class VIII at SMP Mambaul Ulum Bata-Bata. Using a qualitative approach with a case study, data were collected through non-participant observation, interviews with the principal and fiqh teachers, as well as documentation related to student activities and attendance. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the SFE model had a significant impact on student learning and development. This model increases students' critical thinking skills, enthusiasm in learning, and a deeper understanding of the material. Students become more active in asking and answering logical questions in the context of fiqh law, and are able to understand information better. Teachers can also control and monitor students' understanding effectively. Overall, the SFE model not only increases students' interest in learning but also develops their critical thinking skills and mental courage. This model proves to be an effective tool in achieving better learning objectives in the modern educational environment.